Investigating Critical Thinking In Solving Reading Problem - Gadis Dinda Finissha; Yudhi Arifani; Candra Hadi Asmara (Jetlal, 2022)
The capacity of think critically is nedeed for student in learning process because it necessary in this era. Student in this era expected to solve problem in learning process use critical thinking especially in reading. So, in this research “how the process of critical thinking can solve reading problem” become the goal of this study. This study focus on 6 sub-skills of critical thinking based on (Facione, 1990) : interpretation, analysis, inference, evaluation, explanation and self regulation. PISA also conduct in this study for assesment . Descriptive research with qualitative approach apply in this study. Data was collected through a test and interview with all student. Researcher use PISA test to know how student can solve reading problem in comprehension, there are 6 question to analyze 6 sub-skill student critical thinking. The research data was taken from PISA test 2019 and then interview for analyze student process in critical thinking. This research involved 39 students consist of 5 male and 34 female. The subject is student in Thesis and Research Report class University of Muhammadiyah Gresik. The result is student has different way to solve reading problem, student can give different reason for answer the question and student has different analyze for answer question. Several student find way to think critically, such as through find important point of text for think critically, find the keyword of text for comprehend text and then think critically. Reading strategy and type of reading also influnce student comprehension. In further research it can be applied on offline class and use the newest PISA test. The subject in further research can apply in group discussion and using quantitative research.